LAND OWNERSHIP AND USE SYSTEM IN NAGARI KOTO TANGAH, TANJUNG EMAS DISTRICT, TANAH DATAR DISTRICT IN THE VIEW OF FIKIH MUAMALAH - Arfa, Laila; Raus, Afrian; Rizal, Deri (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
The aim of this research is to describe the land ownership and utilization system in Nagari Koto Tangah and analyze the views of muamalah jurisprudence on the land ownership and utilization system in Nagari Koto Tangah. This research is field research (Field Research) with a qualitative descriptive approach. The view of muamalah jurisprudence in obtaining ownership of no-man's land carried out by the people of Nagari Koto Tangah does not fulfill one of the requirements, namely the presence of permission from the Imam or Leader. The management carried out is a form of Syirkah Inan, this form of syirkah is permitted, but the provisions for profit sharing in land management do not meet the provisions for profit sharing in syirkah inan.